Synthesis and Anti-Inflammatory Activity of a Novel Series of Diphenyl-1,2,4-triazoles and Related Derivatives - Swapna Cherala; Harikiran Lingabathula; Rama Ganta; Srinivas Ampati; Sarangapani Manda (E-Journal of Chemistry)
In the present investigation we have synthesized a series of new 1-[3-(4-substitutedphenyl)-5-phenyl-4H-1,2,4-triazol-4-yl]urea and 1-[3-(4-substitutedphenyl)-5-phenyl-4H-1,2,4-triazol-4-yl]thiourea derivatives (4Ia - 4IId). The newly synthesised derivatives were characterized by using the data of IR, 1H NMR and Mass Spectral analysis. Thus synthesised and characterized targetted compounds were further screened for their anti-inflammatory activity by using Carrageenan – induced paw edema rat model. Among all the newly synthesized derivatives, Compounds 4Ia-4Ic and Compounds 4IIa-4IId were reduced the inflammation very significantly (p<0.0001), thus these compounds showed promising anti-inflammatory activity and only one compound (4Id) showed moderate anti-inflammatory activity (p<0.05).